Given that solution for some equation is x=6
Now they want to change x=6 into x=9.
Notice that all equations contans equal sign (=) because both side values are always same.
So if by any chance you want to change value of one side then you must change value on other side too
like we see that 6 changed to 9 by adding 3 on right side then we must add 3 on the left side too
so we get:
x=6
x+3=6+3
x+3=9
Now question says that the left side of the equation stays the same. That is possible only if we move +3 to the right side from the left side so we can write;
x=9-3